WARISAN ANAK ANGKAT MENURUT HUKUM ADAT DAN KOMPILASI HUKUM ISLAM - Mifa Al Fahmi; Hasballah Thaib; Hashim Purba; Rosnidar Sembiring (Universitas Sumatera Utara, 2017)
ABSTRACT Civil law in Indonesia are still pluralism because until now still apply customary law, Islamic law and Western law. The law of inheritance is a part of the law of family who played an important role, even define and reflect the prevailing family system in the community. In this case there are some differences between the existing legal system against the adoption of children in Indonesia. So sometimes becomes an endless discussion towards inheritance for the adopted child. Based on the above background found problems: first the position of adopted children in customary law and Islamic law, second compilation of inheritance adopted children in customary law and Islamic law, third compilation serves parts of adopted children in inheritance law and compile Islamic law. Islamic law is not the presence of adoption so far belies the adoption was done for welfare and education for the child. Adoption does not disconnect from the adopted child with the biological parents. There are no relations between the adopted child to inherit with the adoptive parents. However in the compilation of Islamic law on the set of wills wajibah, so that the adopted child can be given no more than a third of the estate. Unlike the customary law system, the position of adopted children is influenced by the system of kinship or descent, the position of adopted children varies from one region to the other. Adoption can just break the connection of the adopted children against parents, siblings or children of adoption do not disconnect from the adopted child with her biological parents. So is the adopted son of inheritance. Each of the customary law in the area have different settings, there is that because adoption then arises of the relationship between the adoptive parents ' inheritance and vice versa. Similarly, with the portion for adopted children who inherit a system of customary law that the adopted child is given the rights of inheritance from adoptive parents. This inheritance portion against the arrangements differ from one region to the other. Keywords: Inheritance, Adoption, Probate